2023
DOI: 10.3390/foods12020385
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions toward Plant-Based Milk Alternatives among Young Adult Consumers and Non-Consumers in Denmark: An Exploratory Study

Abstract: The objective of this study was to determine associations among plant-based milk alternatives (PBMAs), sources of information on the PBMAs used, and the consumption of PBMAs among Danish young adult consumers and non-consumers of PBMAs. An online survey was conducted in May 2019. A total of 341 participants (consumers: n = 171; non-consumers: n = 170) aged 16–35 years old completed the survey. Most consumers drank less than one glass of PBMAs per week, and oat drink was the most frequently consumed PBMAs. Oat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…For both Pearson’s chi-square test and for binary logistic regression, the p -value was considered significant when p < 0.05 [ 58 ].…”
Section: Methodsmentioning
confidence: 99%
“…For both Pearson’s chi-square test and for binary logistic regression, the p -value was considered significant when p < 0.05 [ 58 ].…”
Section: Methodsmentioning
confidence: 99%
“…Prytulska et al [ 34 ] corroborate the significant impact of health consciousness on favoring PBM. Moreover, Martínez-Padilla et al [ 35 ] found that positive perceptions of PBM’s naturalness, health benefits, and nutritional parity to cow’s milk bolstered its consumption, whereas perceptions of PBM as excessively processed or synthetic deterred consumption. Collectively, these studies underscore the pivotal role of health consciousness in determining PBM consumption trends.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ritchey et al [ 37 ] examined the impact of food neophobia on the acceptance of PBM, concluding that higher levels of neophobia were associated with a lower likelihood of PBM consumption. Faber and Petersen [ 35 ] found that consumers who perceive PBM as natural, healthy, tasty, or nutritionally equivalent to dairy milk are more likely to consume it, whereas those who view it as highly processed or artificial are less likely to do so.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Full-fat cow’s milk has ~3.2–3.7 g/100 mL [ 40 ], whereas partially skimmed and fat-free cow’s milk have lower fat content. There are differences in the fatty-acid composition: a prevalence of saturated fatty acids is typical of cow’s milk (around 60%) and coconut-based drinks (around 90%) [ 10 , 36 ], whereas a prevalence of polyunsaturated fatty acids is reported for soy-based drinks [ 36 ]. Moreover, during the production, different oils (such as sunflower, rice) can be added to improve the organoleptic characteristics, making the lipid profile of the final product different from what could be inferred considering only the primary source.…”
Section: Main Nutritional Characteristics Of Plant-based Milk Alterna...mentioning
confidence: 99%
“…In another qualitative study conducted in Poland, Germany, and France, it was found that barriers and reinforcement to the consumption of plant-based alternatives depend on social factors, including health aspects, peer influences, and country-specific culinary traditions [ 35 ]. An online interview conducted in Denmark among young adults showed that consumers who consider milk and plant-based alternatives nutritionally equivalent are also those who consume them more often [ 36 ]. In a Canadian study based on perceptions and attitudes towards plant-based milk alternatives, plant-based drinks were associated with sustainability and health benefits among participants [ 37 ].…”
Section: Introductionmentioning
confidence: 99%